Investigating ICU nurses’ understanding of incontinence-associated dermatitis: an analysis of influencing factors - Liu Qiang, & Lu Wan Xian, & Pan Yan Bin and & Shan Miao Hang (WCET Journal - Spanish Edition, 2020)
Objective  To investigate the knowledge, attitude and behaviour of ICU nurses in relation to incontinence-associated dermatitis (IAD) in patients with urinary and bowel incontinence. Following this, to identify and analyse any influencing factors to provide a basis for the formulation of standard preventative procedures and preventative nursing strategies for IAD. Methods  Convenience sampling was used to survey ICU nurses’ knowledge, attitude and behaviour towards IAD. Between September and October 2019, a questionnaire designed by the researchers, that also gathered demographic data on the ICU nurses surveyed, was disseminated by the organisation’s information technology processes to 508 ICU nurses. Data were statistically analysed by SPSS22.0 software. Results  The total score obtainable within the questionnaire of staff knowledge, attitude and behaviour was (73.03±7.18). This score matrix was comprised of the following sub scores: knowledge (7.23±1.40), attitude (22.53±3.21), and behaviour (43.27±5.20). The working years of clinical nurses was the main factor influencing the knowledge, attitude and behaviour scores of ICU nurses’ understanding and management of IAD (p<0.05). Multiple linear regression analysis showed that the standard of the IAD prevention and incidence monitoring processes and daily management of IAD were correlating influencing factors of ICU nurses’ total IAD score (p<0.01). Conclusion:  ICU nurses’ knowledge of IAD improved. Similarly, ICU nurses’ attitudes towards IAD was better; however, there were differences between attitudes and practices of IAD. Managers in ICU should be more cognisant of the aetiology of IAD and ensure ICU nurses are educated in associated pathophysiology, risk factors, prevalence and incidence monitoring and root cause analysis of instances of IAD. Further, managers should promote the use of standard prevention and nursing management processes to reduce the incidence of IAD.